2023
DOI: 10.1021/acs.chemrev.2c00762
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic Energy Efficient Windows: Fundamentals, Recent Advances, and Perspectives

Abstract: Thermochromic energy efficient windows represent an important protocol technology for advanced architectural windows with energy-saving capabilities through the intelligent regulation of indoor solar irradiation and the modulation of window optical properties in response to real-time temperature stimuli. In this review, recent progress in some promising thermochromic systems is summarized from the aspects of structures, the micro-/mesoscale regulation of thermochromic properties, and integration with other eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 399 publications
0
26
0
Order By: Relevance
“…When PHC‐Gel hydrogel was placed on a heated plate at 45 °C at 3 s, a rapid transition from transparent to white opaque occurred, and the whole body turned white at ≈9 s, with a response time of ≈6 s. The reason for the above is that PHC‐Gel hydrogel contains temperature‐sensitive PNIPAM and HPC molecular chains inside, and when placed in a high‐temperature environment, it could rapidly form hydrophobic aggregation, resulting in rapid whitening. [ 35–37 ] When the temperature continued to increase, PHC‐Gel still lost water, but the overall morphology did not change significantly. The above results indicate that PHC‐Gel hydrogels have a rapid response to high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…When PHC‐Gel hydrogel was placed on a heated plate at 45 °C at 3 s, a rapid transition from transparent to white opaque occurred, and the whole body turned white at ≈9 s, with a response time of ≈6 s. The reason for the above is that PHC‐Gel hydrogel contains temperature‐sensitive PNIPAM and HPC molecular chains inside, and when placed in a high‐temperature environment, it could rapidly form hydrophobic aggregation, resulting in rapid whitening. [ 35–37 ] When the temperature continued to increase, PHC‐Gel still lost water, but the overall morphology did not change significantly. The above results indicate that PHC‐Gel hydrogels have a rapid response to high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Levinson et al [8] found that using NIR-reflective roof tile coatings can result in a reduction in surface temperature and heat flux. More recently, thermochromic materials, which change their optical properties based on temperature, have been investigated to reduce winter heat loss [9]. Fabiani et al [10] demonstrated that an innovative thermochromic roof configuration can reduce cooling load by 6.59% per square meter, slightly less than a more common cool application, but with no negative effects in winter.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The development of efficient energy conversion technologies is of utmost importance in the modern era, and thermochromic materials are a promising avenue in this regard. 3 In particular, the thermochromic properties of VO 2 have received significant attention in recent years due to their potential for use in various applications, such as temperature sensors, energy harvesting, and cooling devices. The ability of VO 2 to undergo a reversible phase transition from an insulating to a metallic state with a change in temperature makes it an ideal candidate for thermochromic applications.…”
Section: Introductionmentioning
confidence: 99%